Discernment, apropos on dispensation of hospital waste among paramedics: a descriptive study - Agrawal, Swati; Saxena, Vrinda; Jain, Swapnil; Sharva, Vijayta (International Journal Of Community Medicine And Public Health, 2019)
Background: India is one of the most populated and rapidly growing countries in the world and is the source of humongous amounts of waste every year, including municipal solid waste, hazardous waste, biomedical waste or e-waste. Healthcare is one of the largest sectors in India both in terms of revenue and employment. With growing healthcare, there is a requirement of management of bio-medical waste. This study is conducted to assess discernment, apropos on dispensation of hospital waste by paramedics. Methods: A cross-sectional study was conducted to assess the discernment and apropos of paramedical staff in 3 private hospitals regarding disposal of waste in Bhopal city and convenience sampling was used. A total of 204 individuals were approached for the study. The collected data analysed by using SPSS 21.0 and Descriptive analysis was done. Results: Total 204 paramedical staff participated in the study out of which 125 (61.2%) were males and 79 (38.7%) were males. It showed that there was limited level of knowledge, attitude and practices among class 3 workers i.e., attenders as compared to nurses and technicians. Conclusions: Study concluded that there is lack of knowledge about waste management which leads to improper waste disposal and pointed out that class 3 workers have less knowledge as compared to class 1 and class 2 workers. The technicians and nurses comparatively were having better knowledge and attitude, and also practiced waste management better than the attenders.